Diversidad de especies arvenses en plantaciones de Tectona grandis L. f. (teca) de 2 a 8 años de edad en la época seca de los cantones Balzar y Pichincha, año 2018. - Albán Rodríguez, Mery Rubí (2018)
The present investigation was carried out with the objective of determining the diversity of weed species in teak plantations, from 2 to 8 years of age, during the dry season, in the Balzar and Pichincha cantons; Five sites were chosen, where 20 sampling units were established, in which qualitative and quantitative data were taken such as code and description of the species, number of individuals, coordinates of sampling units, in the diversity analysis the presence parameters were considered. and absence, abundance and frequency of species, also the rates of Jaccard, Shannon and Simpson. In addition, a cluster was developed to observe the interactions between sampling sites. The total number of registered individuals was 3421; the families Pocaceae and Fabaceae were the most abundant, the species that had more presence were Desmodium incanum DC., Momordica charantia L., Onoclea sensibilis L., Synedrella nodiflora (L.) Gaertn and Leptochloa scabra Nees. The diversity index showed a greater number of species (34 species) in La colina, being the oldest site (8 years); Jaccard's similarity index presented the highest percentage in Río Grande Pichincha with 47%; cluster analysis revealed three different groups within sites; according to the ANOVA, if there were significant differences between sites, the Student t test of the evaluated indices indicated that there are significant differences between sites (256 m2).